By the Honorable William Pitkin, Esquire ; governor of His Majesty's English colony of Connecticut, in New-England, in America. A proclamation, for a day of public fasting and prayer : ... Wednesday, the nineteenth day of April next ... Given under my hand in Hartford, the ninth day of March ... 1769 (Printed by Green and Watson, near the Great Bridge, 1769)
March 9, 1769 broadside issued by Governor William Pitkin of Connecticut, proclaiming April 19th as a day of public fasting and prayer, directed at the hope that the king and council would look favorably on the petitions of the colony to resolve the discord.